Application of nanotechnology in oil and gas industry: towards enhanced oil and gas recovery - G., Ijeomah; Fahmi, Samsuri; F., Obite; Mohd Anwar, Zawawi (Universiti Malaysia Pahang, 2018)
The global oil demand and the development of advanced techniques have made the regeneration of previously abandoned oilwells economically attractive. As conventional oil recovery methods near their economic limits, a revolutionary new technology is required to harness maximum oil from these stranded oilwells. Due to its potential to manipulate matter at molecular level, nanotechnology promises to dramatically transform oil and gas industry by enabling enhanced oil and gas recovery. Recently, there has been increasing research interest in the applications of nanotechnology in enhanced oil and gas recovery, where the unique aspects of reservoir management, drilling, production, processing and refinery are redesign. Nanotechnology has the potential to revolutionize the drilling process and accelerate the production of oil and gas by providing a platform that makes their separation in the reservoir more amenable. Nanotechnology can make the industry greener by drastically reducing the oil’s carbon footprint in contrast to oils obtained from conventional methods. In this paper, we review the latest trends in the applications of nanotechnology for enhanced oil and gas recovery. We further present scientific advance and new insight into possible future applications. The paper aims to broaden our understanding of the applications landscape of nanotechnology in oil and gas industry.